DECONSTRUCTING PARTICIPATORY SUPERVISION: A STUDY OF PUBLIC INVOLVEMENT STRATEGIES BY THE ELECTION SUPERVISOR BOARD (BAWASLU) IN THE 2024 MAYORAL AND VICE MAYORAL ELECTION IN KUPANG CITY - Adolfus Kobesi; Laurensius P Sayrani; Rudi Rohi (RADJA PUBLIKA, 2026)
This study aims to explain the strategy and form of implementation of participatory supervision carried out by Bawaslu Kupang City in the implementation of the 2024 Pilkada. Using a qualitative research approach method, with a total of 15 informants, consisting of the Chairman of the Bawaslu Kupang City Commissioner, Coordinator of the Prevention, Community Participation and Public Relations Division of Bawaslu Kupang City, Bawaslu Secretariat Staff, Representatives of Bawaslu civil society organizations and community participants in the village/supervisory program. Interviews were conducted with informants selected by purposive sampling, namely those who were considered to best understand the context and have direct involvement in participatory supervision. The results of the study show that participatory supervision carried out by Bawaslu Kupang City in the 2024 Pilkada has shown a paradigm shift from a bureaucratic and hierarchical supervision model to a collaborative model involving the community as supervision partners, through various programs such as the Citizens Forum, Village/Sub-district Supervision, and Participatory Supervision Cadre School (SKPP). The level of public participation in election supervision is still dominated by symbolic and consultative forms of participation, as depicted in Arnstein's ladder of participation, where citizen involvement has not yet fully reached the level of equal partnership or citizen control (citizen power). Deconstruction of participatory supervision also opens up space for conceptual reconstruction, where election supervision is understood as a deliberative process based on communicative action, which demands rational dialogue, equality, and trust between Bawaslu and the community to strengthen the legitimacy of electoral democracy at the local level.